An Injectable Supramolecular Polymer Nanocomposite Hydrogel for Prevention of Breast Cancer Recurrence with Theranostic and Mammoplastic Functions. (14th April 2018) - Wu, Yuanhao; Wang, Hongbo; Gao, Fei; Xu, Ziyang; Dai, Fengying; Liu, Wenguang
Abstract: The high locoregional breast cancer recurrence rate poses a significant risk for patients' survival. Injecting theranostic drugs‐laden soft tissue‐like hydrogels into the resected breast cavity is a promising strategy to achieve both precisely local therapy of breast cancer and reconstructive mammoplasty. In this work, a robust injectable thermoresponsive supramolecular poly( N ‐acryloyl glycinamide‐ co ‐acrylamide) (PNAm) hydrogel bearing polydopamine (PDA) coated‐gold nanoparticles (AuNPs) and doxorubicin (DOX) is fabricated. The supramolecular polymer nanocomposite (SPN) hydrogels exhibit an excellent photothermal effect arising from PDA‐AuNPs that are tightly fixed to the hydrogel matrix via PDA and amide moieties in the network, built‐in near infrared (NIR) light‐triggered gel–sol transition as well as tunable drug delivery. The PNAm‐PDAAu‐DOX sol driven by prior heating is injected into the cavity of resected cancerous breasts of rats where gelation occurred rapidly while the temperature decreased to body temperature, thereby finely serving as a breast filler. During 4 week of implantation, interval NIR light irradiation can mediate photothermal effect and concertedly controllable DOX release, thus collectively preventing the recurrence of breast cancer. Remarkably, this stable remoldable SPN hydrogel facilitates the breast reconstruction and can be tracked by computed tomography (CT) imaging owing to the intrinsic X‐ray attenuation property of the loaded AuNPs. Abstract : A robust injectable suprarmolecular polymer nanocomposite (SPN) hydrogel is synthesized by copolymerization of hydrogen bonding monomers, with addition of polydopamine–gold nanoparticles and doxorubicin. Under near infrared light irradiation, the imageable SPN hydrogel can be injected into the cavity of resected cancerous breast of rats where real‐time photothermal chemotherapy prevents the recurrence of breast cancer, meanwhile realizing breast reconstruction.